Shear bond strength to sound and caries-affected dentin of simplified “etch-and-rinse” and “self-etch” adhesives and the hybrid layer micromorphology - Drobac, Milan R; Stojanac, Igor; Ramić, Bojana; Premović, Milica; Petrović, Ljubomir (Vojnosanitetski pregled, 2021)
Abstract Background/Aim. After removal of caries-infected dentin, a considerable area of the cavity floor comprising caries-affected dentin. Bonding to caries-affected dentin is characterized by lower bound strength and inferior hybrid layer guality compared to bonding to sound dentin. The purpose of study was to compare shear bond strength (SBS) of currently available adhesive systems to sound dentin (SD) and caries-affected dentin (CAD) and elucidate the hybrid layer micromorphology. Methods. Sixty extracted human molars with coronal carious lesions formed the experimental sample while additional sixty extracted intact human molars (impacted third molars) served as controls. Identification of a carious-affected dentin was carried out using visual identification (North Carolina Dentin Sclerosis Scale). Teeth from both the experimental and the control sample were allocated to one of the following three groups: Adper Single Bond Plus/Filtek Supreme XT (ASB/FS) (3M ESPE), AdheSE One/Tetric EvoCeram (AO/TEC) (IvoclarVivadent), and Prime&Bond NT/CeramX Mono (PB/CXM) (Dentsply). Bonding procedures utilized in this work were in line with the manufacturers’ instructions. The SBS was measured using a universal testing apparatus. Hybrid layer micromorphology was observed under scanning electron microscope (SEM). The mean SBS values (MPa), and hybrid layer thickness (in µm) were statistically analyzed using the t-test, Mann-Whitney U-test, ANOVA, and Holm’s test. Results. Mean SBS ± standard deviation were: ASB/FS to SD = 10.56 ± 3.49; ASB/FS to CAD = 10.06 ± 2.55; AO/TEC to SD = 7.01 ± 2.05; AO/TEC to CAD = 6.73 ± 1.66; PB/CXM to SD = 9.01 ± 2.47; PB/CXM to CAD = 7.83 ± 1.42. A statistically significant difference was found between the bonding strength of ASB/FS and AO/TEC to both SD and CAD, and between ASB/FS and PB/CXM to CAD. Hybrid layer thickness was statistically significantly greater for ASB/FS than for PB/CXM. For the ASB/FS system, a statistically significantly thicker hybrid layer was formed on CAD than on SD. No hybrid layer could be observed for AO/TEC. Conclusion. All tested compsite systems bond equally well on sound and caries-affected dentin. The etch-and-rinse adhesives achieved stronger bond strengths. The Adper single Bond Plus-Filtek Supreme XT system formed a statistically significantly thicker hybrid layer on both type 1 of dentin than the Primu 8 Bond NT-CeramX Mono system.